The very hungry celiac : your favorite foods made gluten-free - Persson, Melanie (Hardie Grant Books, 2025)
"In her debut cookbook, Mel shares 75 of her most superb gluten-free recipes for food that is rich, tasty and made to share - and indistinguishable from the gluten-based versions. Mel was diagnosed with celiac disease in her early twenties, and as she began to explore the world of gluten-free cooking, she found that most recipes focused on health and restrictions rather than flavor and texture. She was devastated to think that the foods she had grown up with from Japan and Italy might now be out of reach. As a passionate cook, Mel was determined not to miss out, so she got to experimenting. She spent years in her kitchen perfecting gluten-free versions of the dishes she craved - from fresh pasta to decadent pastries, and udon noodles to baklava."--Amazon.